Validação de um método multirresíduos e multiclasses para determinação e quantificação de 140 resíduos de agrotóxicos em leite através da técnica LC-MS/MS - Fabiano Aurélio da Silva Oliveira (2011)
Milk is a food of animal origin very important to human, widely consumed by children and adults around the world. Often the only available source of protein. Brazilian production has shown increasing in recent decades and this increase in productivity leads to the need for greater control of parasites that infest animals affecting productivity. From the perspective of food safety and considering the reduced number of pesticides monitored by MAPA in milk, there is an urgent need to establish methodologies that can search the presence of multiresidue pesticides in milk. Due to the complexity of the matrix milk and low concentrations of pesticides present in it, there is a great need to develop efficient and reliable analytical methods for identification and quantification of contaminants. This study evaluated four methods of extraction and analysis of pesticide residues in milk, followed by detection and quantification by LC-MS/MS technique. The parameters evaluated were: selectivity, linear response range, limit of detection, limit of quantification, precision and accuracy of the method. The concentration range of analitycal curves was established between 10.0 to 20.0 g.kg-1, with r2 values 0.97. The technique LC-MS/MS in ESI + and ESI- modes promoted quantification (criteria of recovery between 70% and 120% and RSD < 20%) of 140 pesticides in a single chromatographic run. The method was suitable for multiresidue analysis of pesticides in milk, combining sensitivity and selectivity measures, and all the validation parameters were within the limits suggested for validation of chromatographic methods.